A bilayer vascular scaffold with spatially controlled release of growth factors to enhance in situ rapid endothelialization and smooth muscle regeneration. (June 2021) - Wang, Yuanfei; Wu, Tong; Zhang, Jialing; Feng, Zhendong; Yin, Meng; Mo, Xiumei
Abstract: When transplanting a scaffold to repair defected vascular tissues, there is a critical need to achieve in-situ rapid endothelialization together with the circumferential alignment and ingrowth of smooth muscle cells. To this end, we hereby design and fabricate a bilayer vascular scaffold with spatially controlled release of growth factors. The lumen of such a scaffold was made of electrospun poly(l -lactide- co -caprolactone) and collagen (PLCL/COL) nanofibers loaded with uniform heparin and vascular endothelial growth factors (VEGF), while its outer layer was composed of circumferentially aligned, PLCL/COL nanofiber yarns loaded with graded platelet derived growth factors (PDGF) increasing from the outermost toward the interior of the scaffold. With the controlled release of VEGF and PDGF from the scaffold, we showed a continuous greater release percentage ( ca. 15%) of VEGF relative to PDGF over a duration of almost one month in vitro . At two-month post implantation in a rat abdominal aorta defect model, we observed rapid endothelialization at the luminal surface and orientated smooth muscles infiltrating inside the vascular wall. In particular, loose connective tissues rich in collagen fibers were produced at the outermost layer of the vascular scaffold, indicating the capability of such kind of vascular scaffold for in-situ vascular repair or regeneration. Graphical abstract: Unlabelled Image Highlights: A bilayer vascular scaffold was designed with both topographic cues and biological guidance. Vascular endothelial growth factors and platelet derived growth factors were controlled for release. The recruited smooth muscle cells were organized with circumferential alignment. In-situ rapid endothelialization, smooth muscle remodeling, and collagen-rich ECM production were all observed.